Um discurso sobre as atuais configurações familiares em filmes de Almodóvar - Malvestio, Eliana Mantovani (2013)
This research aims to understand the function of the subject feminine at some films of Pedro Almodóvar. In order to do that, this research uses the archaeological theory of Michel Foucault (2012) and his understanding about statement , discursive meaning and archive . This research exposes aspects of this theoretical route to deal with the initial issues: what to elect in the analysis of a filmic collection, since the women are present in almost of the totality of the director‟s work? How to select and relate the filmic scenes and sequences in this universe of images in movement? In this sense, in the universe of twenty movies of Almodóvar, three of them were selected for this analysis: All about my mother (1999), Talk to her (2002) and Volver (2006). As a result, a constant speech that permeates all his work was identified: the practice among female subjects of taking care of their family . This statement, although it seems common, become astonishing in the movies of this director, because it‟s related to the construction of a speech very common nowadays at the Social Science: the new familiar formations derivative from the practices of female care .